A prognostic model and immune regulation analysis of uterine corpus endometrial carcinoma based on cellular senescence - Gao, Lulu; Wang, Xiangdong; Wang, Xuehai; Wang, Fengxu; Tang, Juan; Ji, Jinfeng (Frontiers in Oncology, 2022)
Background This study aimed to explore the clinical significance of cellular senescence in uterine corpus endometrial carcinoma (UCEC). Methods Cluster analysis was performed on GEO data and TCGA data based on cellular senescence related genes, and then performed subtype analysis on differentially expressed genes between subtypes. The prognostic model was constructed using Lasso regression. Survival analysis, microenvironment analysis, immune analysis, mutation analysis, and drug susceptibility analysis were performed to evaluate the practical relevance. Ultimately, a clinical nomogram was constructed and cellular senescence-related genes expression was investigated by qRT-PCR. Results We ultimately identified two subtypes. The prognostic model divides patients into high-risk and low-risk groups. There were notable discrepancies in prognosis, tumor microenvironment, immunity, and mutation between the two subtypes and groups. There was a notable connection between drug-sensitive and risk scores. The nomogram has good calibration with AUC values between 0.75-0.8. In addition, cellular senescence-related genes expression was investigated qRT-PCR. Conclusion Our model and nomogram may effectively forecast patient prognosis and serve as a reference for patient management.